Selection practices in selected academic libraries and its impact on collection development - Rondilla, Rhoel E. (Institute of Library and Information Science, University of the Philippines Diliman, 2002)
Selection is the heart of the collection development process. This core function builds the library's collection for a specific user community. In academic libraries, librarians employed several selection practices in selecting books. These include approval plan, blanket order, bibliographic verification, citation analysis, faculty and student consultation, and the use of finding-aids or selection tools.